Immunization Status, Complications, and Outcome in Children Admitted with Measles at a Tertiary Care Hospital - Riaz ul Haq, Ubedullah Bahalkani, Roshaan Bashir, Saba Wamiq, Asif Javeed, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Measles is a contagious viral infection that impacts children globally, especially in regions with inadequate vaccination rates. Even though it can be prevented with routine immunization, outbreaks and life-threatening complications are still quite common in several developing countries. This study examines the immunization history, the complications, and the clinical outcomes of children diagnosed with measles who were admitted to a tertiary care hospital. Methods: A one-year retrospective descriptive cross-sectional study was carried out from January 2022 till January 2023 at Department of Pediatric Medicine, Multan Medical & Dental College / Ibn-e-Siena Hospital and Research Institute, Multan. The study reviewed medical records from about 1 month to 12 years of age that were clinically diagnosed with measles. Information pertaining to demographic details, nutrition, history of immunization, any related complications, ICU stays, and overall outcomes were retrieved and treated with descriptive and inferential statistics. Results: The study included a sample of 104 children. Measles caseload immunization was as low as 40.4%, with 29.8% partially immunized and an additional 29.8% completely unimmunized. The highest complications were pneumonia (39.4%) followed by diarrhea (28.8%). Cases which required ICU care was 20.2% of the overall caseload. There was a 14.4% mortality rate in the cohort, with the highest deaths occurring amongst children who were non-immunized. Significant statistical correlation was found to exist between immunization status with pneumonia (p = 0.036), diarrhea (p = 0.045), and overall outcome (p = 0.014). Conclusion: The results emphasize the potent link between incomplete immunization and adverse clinical outcomes among children suffering from measles. Complication and mortality rates associated with measles continue to necessitate widespread vaccination as well as prompt identification and intervention for high-risk patients. Keywords: Measles, Immunization, Children, Complications, Outcomes, Hospitalization, Pneumonia, Vaccine Coverage.